Ferrous and non-ferrous metals — A problem of supply or a challenge? - C. -W. Sames (Intereconomics, 1977)
The following article represents an excerpt from a report made by the author on September 30, 1976 to the German-Brazilian Chamber of Commerce in Rio de Janeiro, sponsored by the Fried. Krupp Company. It offers an outlook on the future supply and demand situation for ferrous and non-ferrous metals and identifies a number of factors which might, in the long run, lead to supply problems for the Federal Republic of Germany. Against this background it illustrates the Federal Government's policy for safeguarding the supply with metals vitally needed by the German economy.
Keywords: 330; Raw Materials